Ecological Niche Modeling and Status of Threatened Alpine Medicinal Plant Dactylorhiza Hatagirea D.Don in Western Himalaya. (26th November 2022) - Chandra, Naveen; Singh, Gajendra; Lingwal, Shashank; Jalal, J.S; Bisht, M.S; Pal, Vineet; Bisht, M.P.S; Rawat, Balwant; Tiwari, L.M
ABSTRACT: Medicinal plants are known for their traditional and modern medicinal values to treat health disorders. Dactylorhiza hatagirea (known as Hattajari and Salampanja) is one of these medicinal plants, which is highly praised and valued medicinal plant in alpine regions. The plant has been widely used by the local inhabitants for treating various ailments due to which its demand has increased in the herbal industries. The present study evaluates the distribution and threat status using extensive field surveys and MaxEnt computer package. The distribution was assessed using environmental variables derived from WorldClim data set and slope, aspect, elevation, drainage, soil, geomorphology, land use/land cover (derived from IRS Landsat-8), and 53 well-dispersed field and literature survey species occurrence points. Phyto-sociological information collected using Rapid Mapping Exercise (RME) (50 transects of 500 m in length, each transect having four plots of 1 × 1 m in size at every 50 m distance in east, west, north, and south direction, with a total of 40 plots in one transect) were laid in 26 population sites. The results reveal that the highly suitable habitat of D. hatagirea is only ~177.13 km 2 where the species ranges between 0.1 and 2.2 individual/m 2 in the alpine regions of Uttarakhand Himalaya. However, about 740 km 2 area was found less suitable. Mean diurnal range, aspect, and slope were the most predictor variables for the species occurrence. The collection for domestic use, trade, and habitat loss due to excessive grazing by the heavy-bodied animal was recorded as the major reasons behind the population decline of this medicinally important plant. These findings assist in the identification of new populating and suitable areas for monitoring and in-situ conservation using field survey and range of environment factors that determine the distribution of species.